Report of court proceedings in the case of the anti-Soviet Trotskyite centre. Heard before the military collegium of the supreme court of the U.S.S.R. Moscow, Jan. 23-30, 1937. In re: Y.L. Pyatakov, K.B. Radek, G.Y. Sokolnikov, a.o. Accused of treason against the country espionage. ... Verbatim report (Moscow, 1937)
Karl Radek is pseud. of Karl Berngardovič Sobelson. Publ. by the People's commissariat of justice of the U.S.S.R.